Faktor - Faktor Yang Berhubungan Dengan Infeksi Saluran Pernapasan Akut Pada Balita - Sari, Desi Permata; Asiyah, Siti; Effendi, Hazairin (Jurnal Kebidanan Malakbi, 2024)
Acute respiratory infections are the leading cause of morbidity and mortality due to infectious diseases worldwide. Nearly 4 million people die from acute respiratory infections each year, 98% of which are caused by lower respiratory infections. ARI cases are a concern because they can have serious impacts on the health and development of young children. Although the Pagar Alam City Health Center has made various efforts in prevention and treatment, such as immunization and health education, many ARI cases are still not properly addressed. This indicates the need for a deeper understanding of the factors related to the incidence of ARI in young children in the health center environment. The purpose of this study is to identify the relationship between immunization status, maternal knowledge, and household occupancy density together with the incidence of ARI in young children at the Gunung Dempo Health Center in Pagar Alam City in 2023. The growth of acute respiratory infection cases in South Sumatra Province over the last three years has been significant, as seen in the data: 25,366 cases in 2020, 32,336 cases in 2021, and 519,167 cases in 2022. The method used is cross-sectional with independent data collection to find the relationship between ARI-related factors. The study results show an influence between maternal knowledge and the incidence of ARI, with an odds ratio of 11.66. This indicates that maternal knowledge affects the incidence of ARI, with a Chi-Square p-value result (0.000 < 0.050). ARI incidence is higher in children with incomplete immunization status at 26.7%, and in households with poor occupancy density at 25.8%. From the results of this study, it can be concluded that maternal knowledge, immunization status, and occupancy density are related to the occurrence of ARI cases in young children..